ANALISIS PENGARUH PENGGUNAAN SISTEM PEMBAYARAN DIGITAL DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN - Achmad Fauzi; Shifa Ashila Salwa; Aniar Safitri; Eka Amelia Chiesa Julianti; Sindy Nur Fazriyah (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this research is to find out the interest in using digital payments and also to find out how much interest in digital marketing that is used at this time towards purchasing decisions. The research method is using a systematic literature review method or systematic literature review which can be interpreted that the relationship between Purchase Decisions on the Use of Digital Payments and Digital Marketing, the relationship between the variables Use of Digital Payments and Purchase Decisions, and the relationship between Digital Marketing variables and Purchase Decisions was showing valuable positive relation. And in this research it is also to understand the factors that influence user was having an interest in digital payments and perceptions of trust uploaded through digital marketing.